Occurrence of lactational mastitis and medical management: A prospective cohort study in Glasgow - Scott, Jane; Robertson, M.; Fitzpatrick, J.; Knight, C.; Mulholland, S. (BioMed Central, 2008)
Background: Lactational mastitis is a painful, debilitating condition that if inappropriately managed, may lead women to discontinue breastfeeding prematurely. The aim of this paper is to report the incidence of mastitis in the first six months postpartum in a Scottish population, its impact on breastfeeding duration and to describe the type and appropriateness of the support and management received by affected women from health professionals.Methods: A longitudinal study of 420 breastfeeding women was undertaken in Glasgow in 2004/05. Participants were recruited and completed a baseline questionnaire before discharge from hospital. Cases of mastitis were reported either directly to the researchers or were detected during regular follow-up telephone interviews at weeks 3, 8, 18 and 26. Women experiencing mastitis provided further information of their symptoms and the management and advice they received from health professionals.Results: In total, 74 women (18%) experienced at least one episode of mastitis. More than one half of initial episodes (53%) occurred within the first four weeks postpartum. One in ten women (6/57) were inappropriately advised to either stop breastfeeding from the affected breast or to discontinue breastfeeding altogether.Conclusion: Approximately one in six women is likely to experience one or more episodes of mastitis whilst breastfeeding. A small but clinically important proportion of women continue to receive inappropriate management advice from health professionals which, if followed, could lead them to unnecessarily deprive their infants prematurely of the known nutritional and immunological benefits of breast milk.